Implementasi Manajemen Strategik dalam Meningkatkan Kinerja Guru di Ra Al Ishlahiyyah Wonorejo Pasuruan - Indana Rizki Kamilia; Wahidmurni; M. Fahim Tharaba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to improve teacher performance through aspects of strategic formulation in improving teacher performance in RA Al Ishlahiyyah Wonorejo Pasuruan, strategic implementation in improving teacher performance in RA Al Ishlahiyyah Wonorejo Pasuruan, strategic evaluation in improving teacher performance in RA Al Ishlahiyyah and obstacles in improving teacher performance that can affect the quality of education in the future. This research uses a qualitative approach. Techniques in data collection are using interviews, observations, documentation studies. The subjects in this study were principals and teachers. The results of this study show that 1) strategic formulation in improving teacher performance is to understand the environment of educational institutions both internally and externally and motivate teachers. 2) Strategic implementation in improving teacher performance by involving teachers in training, discussing and sharing knowledge gained when attending training with fellow teachers and holding periodic meetings held by the principal. 3) Strategic evaluation in improving teacher performance is by monitoring and evaluating the administration of the principal will assess or supervise each teacher 4) obstacles to strategic implementation in improving teacher performance some obstacles teachers lack discipline in carrying out the rules that apply in schools, lack of facilities and infrastructure in RA Al Ishlahiyyah Wonorejo Pasuruan. Strategic management can be one of the best alternatives that can be implemented in improving teacher performance in educational institutions.